New species of Anthurium (Araceae) from Chucantí Nature Reserve, eastern Panama - Ortiz, Orlando O.; Baldini, Riccardo M.; Berguido, Guido; Croat, Thomas B. (Phytotaxa, 2016)
In the present paper we describe two new endemic species of Anthurium, discovered during field trips to study the Araceae flora of the Chucantí Nature Reserve (Reserva Natural Chucantí) located in the province of Darién, Panama. Anthurium annularum sp. nov., a member of section Xialophyllium, is principally characterized by its hemiepiphytic climbing habit, stems with ring-shaped nodes with short internodes alternating with much longer internodes, a yellow-green spadix and pale green globose berries which are nearly translucent toward the base. A. chucantiense sp. nov., a member of section Polyneurium, is characterized by its epiphytic habit, short internodes at stem apex, terete petioles, blades with obscure primary lateral veins, greenish to pale orange spadix and narrowly ovoid, and bluntly pointed red-orange berries.